Mutagenic Effects of Sodium Azide on Capsicum anuum L. - Longid, Cecilie (Science Diliman: A Journal of Pure and Applied Sciences; Vol 4 No 1 (1992), 2007)
Dry seeds from pure lines of three varieties of pepper ( Capsicum anuum L.) were treated for 2 hours at 30ÉC with solutions of 0.12, 0.25, 0.50 and O.75 mM sodium azide in phosphate buffer at pH 3. Data in the M 1 show a decrease in germination percentage, height at different stages of growth, number of leaves and seed set. Germination percentage and seed set were reduced significantly. Chlorophyll-deficient seedlings were observed in the M 2 . The most frequent chlorophyll mutations were the viridis type followed by chlorina, xantha and albina. Very few xantha and albina mutants were observed.